La précarité dans la photographie contemporaine : le sujet comme médium - Michele Bertolini (Centre d´Histoire et Théorie des Arts, 2021)
The essay suggests an aesthetic consideration about the contemporary representation of social and economic precariousness. The analysis focuses on three contemporary photographs by Tom Hunter (Woman Reading a Possession Order), Jeff Wall (Insomnia) and Andreas Gursky (Nha Trang Vietnam): the photographs reveal a sophisticated formal construction. Hunter, Wall and Gursky share an interest in the forme tableau dominant during the 1990s in the art photography, nevertheless they deal with the subject in a personal way. Tom Hunter shows the social precariousness by a sacralization of the everyday life and a learned reference to the Vermeer’s pictorial representation. Jeff Wall works on the precariousness and the everyday life as subject and as medium at the same time: the reflexivity is the main notion in the critique theory of Wall. Finally, Andreas Gursky produces an abstract picture of global and social precariousness.